Effects of group kinesiotherapy on primary and secondary symptoms of osteoarthrosis - Camargo, Marcela Regina de [UNESP]; Mantovani, Alessandra Madia [UNESP]; Lopes de Oliveira, Ellene Cristine [UNESP]; Gushiken, Cintia Tiemi [UNESP]; Pizzol, Renilton Jose [UNESP]; Prado Teles Fregonesi, Cristina Elena [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2020)
The aim of this study was to investigate the influence of a specific, kinesiotherapy-based rehabilitation program on the various symptoms of osteoarthrosis (OA), following group treatment. Thirty-one individuals, of both sexes, aged over 50 years and with medical diagnosis of OA, underwent 16 sessions, twice a week, totaling eight weeks, of a specific rehabilitation protocol based on group kinesiotherapy. Primary OA symptoms were assessed (directly related to the disease: OA symptoms, trunk flexibility, balance and pain), and so were secondary ones (indirectly related to the disease: signs of depression and anxiety, and quality of life). Data were tested through Student's t test or Wilcoxon's test, and contingencies of categorical data were analyzed using McNemar's test. There was an improvement in all primary symptoms of OA after the kinesiotherapy protocol was applied. Signs of anxiety and depression improved only in contingency, when risk stratification was taken into account. In addition, physical components of quality of life also showed improvement, which did not occur with mental components though. Therefore, the kinesiotherapy-based rehabilitation program was capable of positively influencing all primary symptoms, and only some aspects of secondary OA symptoms.
Keywords: osteoarthrosis; physiotherapy; exercise therapy; exercise; chronic disease; rehabilitation